Genotypic Variation for Water-Deficit Tolerance in Cotton (Gossypiumhirsutum L.) Germination in Southern Iran. Issue 11 (17th June 2017) - Ghodrat, Vahid; Hamidi, Reza; Alizadeh, Omid; Bazrafshan, Forood; Sharafzadeh, Shahram
ABSTRACT: To determine the effect of water deficit on growth characteristics of 27 cotton cultivars ( Gossypiumhirsutum L.), two separate experiments were performed in laboratory and glasshouse in Fars Province, Zarin-Dasht city (28° 36′ N, 54° 41′ E) in August 2015. In both experiments, which last for 10 days, a completely randomized block design with three replications was used. The main factor was water-deficit levels ((0, −4, and −12 MPa in laboratory and (0 and −8 MPa) in glasshouse experiments), and the subsidiary factor was different cotton cultivars. The sensitivity to water deficit was compared based on factors such as germination rate, shoot and root lengths, fresh and dry weights, seed energy, and seed vigor. The results of both experiments indicated that Oltan, Opal, Pak, Armaghan, Super-Elit Golestan, Super-Elit Bakhteghan, SB-35, Super-Elit Arian, Khandagh, Tabela-18, and Sahel cultivars are more resistant and therefore are suitable candidates to increase plant density and uniformity in the farm.